Current Challenges and Future in Engineering Education - Razdan, P. N. (Journal of Engineering Education Transformations, 2016)
India has one of the youngest populations in the world and a very large pool of young English-speaking people. As per UN World Population Prospects Database 2004, one in five in the world will be Indian with 65% of population below the age of 35 years. Furthermore, as per recent survey, India will become World's 3rd Biggest economy by 2050. Thus we need to create capabilities to meet the skills needs of other countries and also cater to its own demand for trained manpower. Government has already launched "Make in India" campaign with an aim to turn the country into a global manufacturing hub.